Legal Protection Against Consumers In Illegal Cryptocurrency Investments: Edccash Ruling Study - Mochammad Fabian Athaya; Joanita Jalianery; Ariani Yestati (Eduvest - Journal of Universal Studies, 2026)
The advancement of digital technology has driven the emergence of cryptocurrency as a new investment instrument that promises high accessibility and potential returns. However, this development also creates legal risks for consumers, particularly when transactions are carried out through illegal platforms that operate outside government supervision. This study aims to examine the legal reasoning used by judges in determining unlawful acts in illegal cryptocurrency transactions and to assess the effectiveness of civil legal protection for consumers. The research employs a normative juridical method using statutory, case, and conceptual approaches. The results indicate that the application of consumer protection principles and the construction of civil liability provide legal certainty for victims, despite the limited regulatory framework governing crypto assets in Indonesia. The novelty of this study lies in the application of the Digital Consumer Vulnerability Theory (DCVT) as an analytical framework to identify digital consumer vulnerabilities arising from information asymmetry, technological opacity, regulatory vacuum, and psychological manipulation in crypto investment schemes. This research highlights the need for a more adaptive and comprehensive legal approach to ensure consumer protection in the digital era.